Absence of embedded mass shells: Cerenkov radiation and quantum friction - De Roeck, Wojciech; Fröhlich, Jürg; Pizzo, Alessandro (Annales Henri Poincaré, 2010)
We show that, in a model where a non-relativistic particle is coupled to a quantized relativistic scalar Bose field, the embedded mass shell of the particle dissolves in the continuum when the interaction is turned on, provided the coupling constant is sufficiently small. More precisely, under the assumption that the fiber eigenvectors corresponding to the putative mass shell are differentiable as functions of the total momentum of the system, we show that a mass shell could exist only at a strictly positive distance from the unperturbed embedded mass shell near the boundary of the energy-momentum spectrum.
Gesehen am 15.09.2023